Unlikely Police chief: from and to Jaisalmer house - Vohra, B. L. (New Delhi Konark, 2023)
In this autobiography, the author narrates the story of his life as a police officer, starting from his childhood, to joining the coveted IPS, and finally to his retirement. As a refugee toddler from Pakistan, his early memories go back to living in a camp in Delhi (India)
Keywords: B.L. Vohra, IPS; Autobiography